1996
DOI: 10.1017/s1068280500000010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Market Integration: Definition, Theory, and Evidence

Abstract: A point-space model of interregional trade is used to define market integration and to explore its implications for modeling spatial price relationships. This analysis indicates that spatial prices are related nonlinearly, contrary to much of the work on spatial price analysis which uses linear models. As an empirical example, corn market integration along the Mississippi River is examined during the Midwest flood of 1993. Higher transport costs during this period significantly reduced the extent of integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 12 publications
0
45
0
5
Order By: Relevance
“…However, these transactions costs are assumed to be stationary and proportional to traded volumes to facilitate the construction of linear models. Relaxing this assumption calls for models that include thresholds (McNew 1996, Barrett and Li 2002, Brooks and Melyukhina 2003. Trade policies affect price transmission through intervention instruments such as nontariff barriers, tariff rate quotas, prohibitive tariffs, etc.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…However, these transactions costs are assumed to be stationary and proportional to traded volumes to facilitate the construction of linear models. Relaxing this assumption calls for models that include thresholds (McNew 1996, Barrett and Li 2002, Brooks and Melyukhina 2003. Trade policies affect price transmission through intervention instruments such as nontariff barriers, tariff rate quotas, prohibitive tariffs, etc.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…The main defenders of this school are: [15]- [20]. According to Mc New [17], linearity of bivariate was inappropriate to test the integration of markets. Mc New and Fackler [18] showed that the price series on two integrated markets were not necessarily co-integrated.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…Determining whether markets are integrated, and assessing the level of integration with statistical indicators, often requires setting somewhat arbitrary thresholds (e.g., Harriss 1979). In other words, as noted by McNew (1996), market integration is more frequently premised upon statistical criteria than economic phenomena.…”
Section: Market Integration and The 2004/5 Food Crisis In Nigermentioning
confidence: 99%